(untitled) (Filologia e Linguística Portuguesa, 2010)
This article presents a sample of the differences found in editions from the same literary works written by national writers, which have raised doubts in relation to the original texts used by the publishing houses. The diversity of texts from the same literary work has led us to research the sources: the originals used by the author, editions revised by the author, some editions altered by the editors or even the vast number of errors introduced during the document´s printing tradition. The article concentrates on the survey, due to the impossibility of developing a deeper and more specialized research into each literary work. However, with the support of relevant bibliography, it proposes a classification of problems found.